(untitled) (Revista Sistemas de Producción Agroecológicos, 2011)
Recent years, efforts have intensified the search for sustainable technologies that can recover and maintain the productive potential of degraded areas and diversify the range of products to allow greater competitiveness. In this aspect, which has highlighted the agroforestry as a sustainable alternative to the productive processes of agriculture. Agroforestry systems (AFS), are ways of using and managing natural resources in which woody species (trees, shrubs, palms) are deliberately used in association with crops or animals in the same area, simultaneously or in a temporal sequence. Among the benefits of agroforestry include: reduced soil degradation, improved soil fertility with increased organic matter and nitrogen supply, control of adverse environmental conditions (winds, excessive temperatures, evaporation of water resources, etc.), shade and food for animals and availability of marketable products. For this reason, it has been postulated that more accurately silvopastoral SAF, have been combined in various ways for livestock with trees to different purposes, responding in part to the problems of deforestation and degradation of ecosystems and the sustainability of livestock. Nitrogen fixing trees appear as particularly promising to reduce degradation and increase sustainable in the production of animal protein.